Pertanggungjawaban Pidana Terhadap Debt Collector (Penagih Hutang) Melakukan Tindak Kekerasan Dalam Penagihan Yang Bermasalah - Deny Syaputra; Tri Putra Perkasa; Fawez Farhan Dani; Siddik Andrean; Didit Selamat Raharjo (Consensus : Jurnal Ilmu Hukum, 2022)
Although the credit system is very beneficial for society and the country's economic growth, not all goods sold in stores today have a credit system. In addition to the trust factor, there are other factors that make it easier for buyers to buy money than credit. But even though it is simple, this is a problem because if we are not responsible for paying debts, we are dealing with debt collectors who collect our debts. According to the author, harassment, threats, confiscation of property, even beatings and torture are some types of violence carried out by debt collectors. It is clear that the actions of debt collectors are a violation of the law. To stop the criminal acts of debt collectors, law enforcement and the community must work together. In this case, the community must participate actively. They must immediately report any criminal acts committed by debt collectors.